Report of the Center-Commissioned External Review (CCER) of the International Service for National Agricultural Research (ISNAR) Division - Heidhues, Franz; Mule, Harris (International Food Policy Research Institute, 2007)
Following CGIAR’s decisions at its Annual General Meeting in October 2003 to merge ISNAR with IFPRI and to relocate operations from The Hague to Addis Ababa, the new ISNAR, as a Division of IFPRI, came into being on April 1, 2004. A Program Advisory Committee (PAC) was established to provide guidance on the ISNAR research and program development. To manage the integration of ISNAR within IFPRI, a Special Advisor to the Director General of IFPRI was recruited on a four month consultancy from April, 2004. The complex process of the merger, involving many players – the CGIAR, the Science Council, the Board of IFPRI and ISNAR, the Senior Management of the two institutions, relocation of ISNAR to a new site, and hosting of ISNAR to ILRI was handled efficiently within a short period of 6 months. This review was carried out in July – September 2007 upon the recommendation of the External Program and Management Review of IFPRI.